Whole-genome resequencing revealed the genetic diversity and body weight-related genes of Gannan yak - Minghao Zhang; Minghao Zhang; Chun Huang; Chun Huang; Qi Bao; Tong Wang; Tong Wang; Xiaoming Ma; Xiaoming Ma; Guangyao Meng; Guangyao Meng; Xuelan Zhou; et al. (Frontiers in Veterinary Science)
Body weight (BW) is a crucial indicator of animal growth and development, significantly influencing animal husbandry practices. Previous research has identified several genes associated with BW in certain yak breeds. However, the genetic basis of BW in Gannan yaks has not been reported. In this study, 309 yaks from six breeds across five provinces in China were sampled. This collection included 247 54-month-old female Gannan yaks, along with 20 Xizang yaks, 15 Muli yaks, 10 Pamir yaks, 9 Bazhou yaks, and 8 Zhongdian yaks. Body weight measurements were recorded for the Gannan yaks. Initial analyses of runs of homozygosity (ROH), nucleotide diversity, and linkage disequilibrium (LD) decay among the six yak breeds revealed that Gannan yaks exhibited the lowest ROH, the highest nucleotide diversity, and the fastest LD decay, indicating rich genetic diversity. Subsequently, a genome-wide association study (GWAS) identified 19 BW-related genes in the Gannan yaks, with PMAIP1, GABBR1, LRPPRC, and PPP1R11 identified as key genes. Genome-wide scanning of Group 1 and Group 2 (detailed in section 2.4) identified 90 genes, and Gene Ontology (GO) analysis highlighted FGF2, SHH, and WNT11 as significantly associated with growth, development, and metabolism. Three overlapping genes were identified between GWAS and genome-wide scans. Further analyses, including nucleotide diversity, LD analysis of significant GWAS sites, allele frequency analysis, and SNP association studies, suggested that DRC1 and SELENOI are novel candidate genes for BW in Gannan yaks. These findings provide a molecular foundation for the genetic improvement of Gannan yaks.